A new framework based on XFEM for cracked semipermeable piezoelectric material. (August 2021) - Jena, J.; Singh, S.K.; Gaur, V.; Singh, I.V.; Natarajan, S.
Highlights: A novel load-controlled iteration scheme is proposed within the XFEM framework for semipermeable piezoelectric material. Interaction integral approach is used to evaluate the electric displacement intensity factor (EDIF). Effect of polarization angle, crack length, loading parameter is investigated on the electric displacement intensity factor. EDIF results show an excellent agreement with the results obtained from the iterative capacitor analogy (ICA). Abstract: In the present work, a novel load-controlled iteration scheme within the framework of extended finite element method (XFEM) is proposed to model the semipermeable crack in a piezoelectric material. To capture the stress and electric displacement singularity at the crack tip, the electromechanical 6-fold enrichment functions are used. The domain form of electromechanical interaction integral is employed to determine the generalized intensity factor. The accuracy of a proposed scheme based on XFEM is validated against the reference solutions derived from the iterative capacitor analogy (ICA) method. The effect of several crack configurations, polarization angle, far-field mechanical and electrical traction on electric displacement intensity factor (EDIF) are analyzed for cracked semipermeable piezoelectric material.